2016
DOI: 10.1111/jmft.12178
|View full text |Cite
|
Sign up to set email alerts
|

Couples Therapy for Intimate Partner Violence: A Systematic Review and Meta‐Analysis

Abstract: Intimate partner violence is a serious public health problem accompanied by substantial morbidity and mortality. Despite its documented impact on health, there is no widely recognized treatment of choice. Some studies indicate that couples suffering from situational violence may benefit from couples therapy, but professionals are cautious to risk the possibility of violent retaliation between partners. After a comprehensive literature search of 1733 citations, this systematic review and meta-analysis compiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
80
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 44 publications
0
80
0
3
Order By: Relevance
“…We acknowledge the controversy that exists surrounding a couple's systems approach to treatment when intimate partner violence or child abuse has been identified (Mahraj, ; Stith & McCollum, ). However, a comprehensive review of studies indicates that working with couples conjointly is efficacious and appropriate in some situations (Karakurt, Whiting, Esch, Bolen, & Calabrese, ), such as when situational violence rather than coercive control is involved (Hardesty, Crossman, Khaw, & Raffaelli, ). With careful monitoring for safety concerns, our intervention supported couples work on communication issues, negative attributions, and self‐control of aggression.…”
Section: The Present Studymentioning
confidence: 99%
“…We acknowledge the controversy that exists surrounding a couple's systems approach to treatment when intimate partner violence or child abuse has been identified (Mahraj, ; Stith & McCollum, ). However, a comprehensive review of studies indicates that working with couples conjointly is efficacious and appropriate in some situations (Karakurt, Whiting, Esch, Bolen, & Calabrese, ), such as when situational violence rather than coercive control is involved (Hardesty, Crossman, Khaw, & Raffaelli, ). With careful monitoring for safety concerns, our intervention supported couples work on communication issues, negative attributions, and self‐control of aggression.…”
Section: The Present Studymentioning
confidence: 99%
“…Young Parenthood Program(YPP, Florsheim et al, 2012); Couples Therapy for Intimate Partner violence,Karakurt, Whiting, Esch, Bolen, & Calabrese, 2016; Child Parent Psychotherapy (CPP, Lieberman et al, 2005)]. 2.…”
mentioning
confidence: 99%
“…In a meta‐analysis of six studies, Karakurt et al . () found that couple therapy was more effective than alternative interventions for mild‐to‐moderate situational intimate partner violence, with an effect size of 0.84. Karakurt included studies of psychoeducational, behavioural, and solution‐focused couple therapy in this meta‐analysis.…”
Section: Intimate Partner Violencementioning
confidence: 99%